Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1080/10410236.2010.521913
|View full text |Cite
|
Sign up to set email alerts
|

Public Health Framing of News Regarding Childhood Obesity in the United States

Abstract: Five U.S. newspapers were searched for stories regarding childhood obesity. Of the 201 stories appearing in 1996, 2001, or 2006, 97 incorporated a public health frame (i.e., connects problem to the larger social and environmental context; exposes risk factors; includes information regarding preventatives and correctives). Significant risk factors were identified as unhealthy eating practices, lack of physical activity, and ads for junk food directed at children. Prevalent categories of preventatives and correc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 24 publications
3
35
0
Order By: Relevance
“…Consequently, consenting to the take by Mattson and Basu (2010) that any course needs to "remain cognizant of the importance of messages" (p. 276). The findings are in agreement with studies by Cohen (2010); Hawkins and Linvill (2010); Kahneman and Tversky (1979);Carrera et al (2010), showing that vast sources have indeed provided vast breast cancer messages, messages that respondents have assessed in terms of probable gains and/or losses, of course with influence of demographic factors, thus explaining different perceptions and behaviour executed by the women.…”
Section: Message Framessupporting
confidence: 81%
“…Consequently, consenting to the take by Mattson and Basu (2010) that any course needs to "remain cognizant of the importance of messages" (p. 276). The findings are in agreement with studies by Cohen (2010); Hawkins and Linvill (2010); Kahneman and Tversky (1979);Carrera et al (2010), showing that vast sources have indeed provided vast breast cancer messages, messages that respondents have assessed in terms of probable gains and/or losses, of course with influence of demographic factors, thus explaining different perceptions and behaviour executed by the women.…”
Section: Message Framessupporting
confidence: 81%
“…Thematic approaches help individuals relate to stories and understand how they connect them with other people (Drewnowski, 2009;Levine, 2011). Journalists, particularly those covering health and science, have been repeatedly encouraged to include thematic frames in their news coverage (see Hawkins & Linvill, 2010).…”
Section: News Representationsmentioning
confidence: 99%
“…News reporting about obesity has increased dramatically in the last 10 to 20 years (Campos, Saguy, Ernsberger, Oliver, & Gaesser, 2006;De Brún, McKenzie, McCarthy, & McGloin, 2012;Gearhart, Craig, & Steed, 2012;Hawkins & Linvill, 2010;Kersh & Morone, 2005;Kim & Willis, 2007;Lawrence, 2004;McClure, Puhl, & Heuer, 2010;Puhl & Heuer, 2009). Although news reporting about obesity draws heavily on scientific information and the opinions of obesity researchers (Saguy & Riley, 2005), a number of studies have shown that there might be problems with the news reporting of this complex health issue.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers suggest that the news stories focus more on personal responsibility and self-control, rather than on the broader social and environmental determinants of weight gain (Ata & Thompson, 2010;Hawkins & Linvill, 2010;Kim & Willis, 2007;Saguy & Gruys, 2010). Some researchers have noted increasing frequency of frames 2 such as mixed frames and environmental frames (De Brún et al, 2012) and emergent frames such as fatalism (Shugart, 2011) and culture (Shugart, 2013).…”
Section: Introductionmentioning
confidence: 99%